Pemberdayaan Para Penyandang Disabilitas Rungu Melalui Keterampilan Kerja di Kedai Difabis Coffee and Tea Kendal Jakarta Pusat - Salwa Sabilah; Almisar Hamid (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Issues regarding people with disabilities in the world of work are still often overlooked, leading to minimal job opportunities for people with disabilities. As a result, many individuals with disabilities face high unemployment rates. According to the International Labour Organization (ILO), 82% of people with disabilities in developing countries live below the poverty line. They experience significant challenges accessing employment, healthcare, information, and political participation, often facing fewer job opportunities than individuals without disabilities. The National Zakat Agency (BAZNAS BAZIS) DKI Jakarta Province is one of the institutions that focuses on empowering people with disabilities through its Difabis program. The program serves as a platform for people with disabilities to train their work abilities, engage in learning, express creativity, and gain equal employment opportunities. This study aims to examine (1) How Difabis Coffee and Tea has implemented programs to empower people with disabilities, (2) What types of skills training are provided by Difabis Coffee and Tea to empower people with disabilities, and (3) What supporting factors and leadership factors influence the effectiveness of the empowerment process at Difabis Coffee and Tea. This research employs a qualitative approach, using data from observations, interviews, and documentation. The results of the study indicate that the empowerment provided by Difabis Coffee and Tea through skills training has led to positive changes for individuals with disabilities. Participants who once felt helpless now have greater independence, self-confidence, improved communication skills, and an income from the skills they have developed.